Mini trainer speed sensor: Validation of learning media - Debataraja, Daniel Parningotan; Basri, Irma Yulia; Rifdarmon, Rifdarmon; Nanda, Iffarial (Research in Education and Technology (REGY), 2024)
The problem of this research was the limitation of learning media for speed sensors in the Ototronics laboratory, which has an impact on three critical aspects in the teaching and learning process: (1) limited students gain practical experience, (2) decreased student motivation and participation, and (3) the difficulty of lecturers demonstrating material comprehensively in the Sensors and Transducers course. This research aimed to design a mini trainer speed sensor as an innovative learning media to overcome the limitations of practicum media in the Ototronics laboratory, impacting the student learning experience. The research used a quantitative-descriptive and Structural Equation Modeling-Partial Least Squares (SEM-PLS) validation involving 7 learning media experts. The results showed highly significant design validity. The didactic aspect proved to give the most superior contribution to improving the effectiveness of learning media. This research successfully addressed three main problems: student’s limited practical experience, decreased participation motivation, and lecturers’ difficulty demonstrating the material. The results confirm that this particular learning media effectively addresses three critical impacts in the teaching and learning process: student’s limited practical experience, decreased participation motivation, and lecturers’ difficulty demonstrating the material, thus opening up opportunities for developing transformative interactive learning media in technical vocational education.